LEGAL IMPLICATIONS OF THE APPLICATION OF THE ONE-TIER BOARD SYSTEM ON THE MANAGEMENT ORGANS OF INDIVIDUAL COMPANIES - Aida Nur Hasanah; Uswatun Hasanah (LPPM STIH Putri Maharaja, 2025)
The implementation of Law Number 6 of 2023 concerning Job Creation offers Micro and Small Enterprises the opportunity to formalize their operations as legal organizations, namely as Individual Companies. Individual Companies have the same legal-entity concept as a Limited Liability Company, with limited liability. The management structure of a sole proprietorship uses a one-tier board system, in which the functions of commissioners and directors are integrated into a single entity. This research aims to explain the application of the one-tier board system in Indonesian sole proprietorships and to analyze its legal consequences for the company's management organs. This includes an examination of the legal entity status, management responsibilities, supervision and accountability, legal relationships with third parties, and financial and tax regulations. The results of the research show that an individual company provides legal entity status and limited liability protection for MSEs through simplified establishment procedures without the obligation of a notarial deed. The application of the one-board tier system optimizes decision-making efficiency. Still, it eliminates the function of internal control (checks and balances) by merging all organs of the company, which can increase legal risk and expose the company to potential liability piercing the corporate veil in the event of bad faith or managerial malpractice.